STATISTICAL ANALYSIS AND ASSESSMENT OF FUNGAL-INDUCED DETERIORATION IN SELECTED MONUMENTS OF PRAYAGRAJ - Soni, Rahul; kumar, Ashish; Pandey, Amita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines fungal-induced deterioration of selected historical monuments in Prayagraj, India, with a focus on Aspergillus niger, Penicillium chrysogenum, and Fusarium species. Five significant monuments had surface samples taken, which were then examined using morphological and molecular identification techniques. High humidity and fungal proliferation were found to be strongly correlated by statistical studies such as ANOVA, Pearson correlation, and diversity indices; Khusro Bagh had the highest fungal diversity. Biogenic mineral dissolution and structural degradation were confirmed by Fourier Transform Infrared Spectroscopy (FTIR) and Environmental Scanning Electron Microscopy (ESEM). High humidity and fungal growth were found to be significantly correlated (p<0.05) by statistical analysis, highlighting the impact of the environment on biodeterioration. The study highlights synergistic interactions among fungal species, contributing to accelerated biodeterioration. These findings underscore the urgency of implementing effective biocontrol measures and preventive maintenance to safeguard cultural heritage from fungal degradation.